Iranian Household Financial Protection against Catastrophic Health Care Expenditures - M Nekoei Moghadam; M Banshi; M Akbari Javar; M Amiresmaili; S Ganjavi (Tehran University of Medical Sciences, 2012)
Background: Protecting households against financial risks is one of objectives of any health system. In this regard, Iran's fourth five year developmental plan act in its 90th article, articulated decreasing household's exposure to catastrophic health expenditure to one percent. Hence, this study aimed to measure percentage of Iranian households exposed to catastrophic health expenditures and to explore its determinants. Methods: The present descriptive- analytical study was carried out retrospectively. Households whose financial contributions to the health system exceeded 40% of disposable income were considered as exposed to catastrophic healthcare expenditures. Influential factors on catastrophic healthcare expenditures were examined by logistic regression and chi-square test. Results: Of 39,088 households, 80 were excluded due to absence of food expenditures. 2.8% of households were exposed to catastrophic health expenditures. Influential factors on catastrophic healthcare were utilizing ambulatory, hospital, and drug addiction cessation services as well as consuming pharmaceuticals. Socioeconomics characteristics such as health insurance coverage, household size, and economic status were other determinants of exposure to catastrophic healthcare expenditures. Conclusion: Iranian health system has not achieved the objective of reducing catastrophic healthcare expenditure to one percent. Inefficient health insurance coverage, different fee schedules practiced by private and public providers, failure of referral system are considered as probable barriers toward decreasing households' exposure to catastrophic healthcare expenditures.